YAHQI: SEBAGAI METODE PEMBELAJARAN HAFALAN HADIS BAGI SISWA KELAS IV SDI CENDEKIA ASSALAM BANGILAN TUBAN - Siti Effi Nur Ummah; Zulfatun Anisah; Vita Fitriatul Ulya; Ahmad Suyanto (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to determine 1) Hadith memorization learning process through the Yahqi Method for fourth grade students of SDI Cendekia Assalam Bangilan Tuban, 2) The results of hadith memorization through the Yahqi Method for fourth grade students of SDI Cendekia Assalam Bangilan Tuban, and 3) Supporting and inhibiting factors in learning. memorization of hadith through the Yahqi Method Fourth grade students of SDI Cendekia Assalam Bangilan Tuban. In this study, researchers used descriptive qualitative methods, data collection techniques used in this study include observation, interviews, and documentation. After that, the data was analyzed by reducing the data, displaying the data, then verifying it. The results of this study indicate that 1) The process of memorizing hadith through the Yahqi Method includes the implementation of memorizing hadith learning carried out on Mondays and Fridays after the Duha prayer, 2) The implementation of memorizing hadith learning using special techniques, and 3) how to deliver learning materials using jiharka and rhythmic rhythms. movement with 4 steps. The results of learning to memorize hadith through the Yahqi Method showed students were able to memorize 14 hadiths in one semester. Supporting factors in learning to memorize hadith include 1) The material is suitable to be applied at the age of children, 2) using movements that are in accordance with the meaning, 3) using rhythms that increasingly liven up the atmosphere, and 4) Children memorize easily and quickly. While the inhibiting factors in learning to memorize hadith through the Yahqi Method are 1) limited time and 2) various narrators making children often confused and forgetting. Keywords: Learning, Hadith Memorization, Yahqi Method